Attitudes in the general population towards hemi-craniectomy for middle cerebral artery (MCA) infarction: a population-based survey - Klein, Anne; Kühner, Christine; Schwarz, Stefan (Neurocritical care, 2012)
Background: Decompressive hemicraniectomy reduces mortality after space-occupying MCA infarction. Data on the general public’s opinion toward interventions that can save lives but leave the survivors impaired are lacking. Methods: In this population-based epidemiological study in a German city, we surveyed 312 adults in a telephone interview. Here, we presented a scenario of a space-occupying MCA infarct. We evaluated probands’ attitude toward decompressive surgery in general, and toward outcome scenarios according to Rankin scale (RS) definitions. Results: 312 persons (157 women, 52 ± 20 years) were interviewed. 58 persons had difficulty comprehending the proposed scenario, most of them being of advanced age (79 ± 5 years). From the remaining 254 responders 5 (2%) persons favoured surgical intervention, 149 (58%) were undecided, and 100 (39%) were opposed to surgery. The number of individuals opting for surgery rose in scenarios with a better outcome: If very severe impairment was anticipated (RS 5), only 3 (1%) persons favored surgery. With severe (RS 4), moderate (RS3), and slight impairment (RS2) the numbers were at 16 (6%), 60 (24%), and 161 (63%), respectively. We found no association with age, sex, religion, education, self-estimated health status, or marital status. Conclusions: Explaining complex medical situations to laypersons poses a major problem, particularly to those of old age. Only a minority favors life-saving medical interventions if survival is associated with deficits of unpredictable degree. The majority of persons does not favor intervention even if only moderate impairment is anticipated. Decompressive surgery may in fact be against the values of many individuals.